Digital Entrepreneurial Orientation and Organizational Performance: The Mediating Role of Digital Innovation Competence and The Moderating Effect of Digital Technology Preparedness - Purnawan, Medi Primatori; Rachbini, Widarto; Mu’min , Halek; Darmanto (International Journal of Accounting and Economics Studies, 2025)
This research examines the relationship between digital entrepreneurial orientation and organizational performance in Indonesian healthcare organizations, investigating the mediating role of digital innovation competence and the moderating effect of digital technology preparedness. Using PLS-SEM with 250 healthcare organizations in Batam City, the study tests an integrated moderated mediation model grounded in resource-based view, dynamic capabilities theory, and contingency theory. Results demonstrate that digital entrepreneurial orientation significantly influences organizational performance both directly and indirectly through digital innovation competence as a partial mediator. Digital technology preparedness serves as a critical moderator, substantially amplifying the relationship between entrepreneurial orientation and innovation competence at higher preparedness levels. The model explains substantial variance in digital innovation competence and moderate variance in organizational performance, demonstrating strong predictive relevance. These findings contribute to digital entrepreneurship theory by revealing conditional indirect mechanisms through which entrepreneurial orientation creates value in digital transformation contexts. The research extends understanding of how organizational capabilities mediate strategic orientation effects while technological readiness serves as an enabling condition. Practically, Indonesian healthcare organizations should prioritize developing comprehensive digital innovation competencies while simultaneously investing in technological infrastructure, human capital, and organizational culture to maximize entrepreneurial benefits. The study provides actionable insights for healthcare managers navigating digital transformation challenges in emerging markets, emphasizing capability-building approaches over purely strategic positioning.